Design of IoT-Based Battery Monitoring for DC Backup - Yunidar, Yunidar; Fathurrahman, Fathurrahman; Melinda, Melinda; Azra, Ery; Malahayati, M.; Elizar, Elizar (Green Intelligent Systems and Applications, 2024)
The battery monitoring process for the DC backup power supply at the Banda Aceh Main Substation was previously performed manually using a multimeter, leading to inefficiencies. This study aimed to develop an automated battery monitoring system based on the Internet of Things (IoT) to enhance operational efficiency. The proposed system integrated a DC voltage sensor (voltage divider) connected to the battery and an INA219 sensor to measure current flow during battery usage. A NodeMCU ESP8266 microcontroller, programmed with the Arduino IDE, served as the main data processor and internet interface. Monitoring data was transmitted to officers via an IoT-based cloud server on the Blynk platform. The system was tested using eight NiCd 1.2 V battery cells arranged to simulate the substation setup. The resulting prototype automated daily battery monitoring, significantly improving the efficiency and effectiveness of the monitoring process.